1992
DOI: 10.2307/3431256
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Monitoring of Human Polymorphic Cancer Susceptibility Genes by Polymerase Chain Reaction: Application to Glutathione Transferase m

Abstract: Several genes involved in the metabolism of carcinogens have been found to be polymorphic in human populations and are associated with increased risk of cancer at some sites. This study focuses on the polymorphic enzyme glutathione transferase mu (GT mu). Smokers with low lymphocyte GT mu activity are at an approximately 2-fold higher risk for lung cancer and an approximately 3-fold higher risk for stomach and colon adenocarcinomas. Recent cloning and sequencing of the GST1 gene has allowed the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
(15 reference statements)
2
14
0
Order By: Relevance
“…About 50% of the Caucasian population inherits two deficient alleles (i.e., they are homozygous for the null allele of the gene) and are thus devoid of GSTM1 activity. The GSTMI null genotype frequency has been reported to show marked ethnic variation (51). Individuals lacking GSTM1 could be at a greater risk for developing lung cancer due to deficient detoxification processes; this notion is supported by recent studies (52).…”
Section: Ahr and Arnt Genessupporting
confidence: 72%
See 1 more Smart Citation
“…About 50% of the Caucasian population inherits two deficient alleles (i.e., they are homozygous for the null allele of the gene) and are thus devoid of GSTM1 activity. The GSTMI null genotype frequency has been reported to show marked ethnic variation (51). Individuals lacking GSTM1 could be at a greater risk for developing lung cancer due to deficient detoxification processes; this notion is supported by recent studies (52).…”
Section: Ahr and Arnt Genessupporting
confidence: 72%
“…There are, however, several putative confounding factors that are known to affect the phenotype such as environmental exposures, nutrition, and differences in smoking habits (56). In recent genotyping studies using PCR assays (51), no association has been found between null genotype and lung adenocarcinoma, but a tendency for an association between the GSTMI genotype and squamous cell carcinoma has been reported (57)(58)(59). GSTT1 Recently a GST null phenotype unrelated to the GSTMI was described for the glutathione-dependent detoxification of naturally occurring monohalomethanes.…”
Section: Ahr and Arnt Genesmentioning
confidence: 99%
“…In this context, environmental tobacco smolce should also be considered (35) in that it contains at least 17 different mono-and bicyclic aromatic amines, including 2-naphthylamine and 4-aminodiphenyl (36). 011 the other hand, recent studies on the polyrnorphisrn of the huinan glutathione transferase GSTM1 (37) and its relevance to human lung (38) and bladder (39) cancer have introduced the concept that the GSTMl gene ought to have a protective role in tobacco-induced bladder cancer, possibly through increased detoxification of biologically reactive i~lternledlates of polycyclic aromatic hydrocarbons.…”
Section: Discussionmentioning
confidence: 99%
“…In order to detect the GT p. sequence polymorphism by PCR, we used oligonucleotide primers that amplify exons 4-5 (8,12) or exons 6-7 of the GST1 gene. PCR amplification with these primer sets produced 273-bp or 215-bp bands on agarose gels from individuals with one or two copies of the GST1 allele, and no visible band if the individual was homozygously deleted.…”
Section: Resultsmentioning
confidence: 99%